Komunikasi Dosen dengan Mahasiswa Kelompok Digital-natives di Perguruan Tinggi - Indra Novianto Adibayu Pamungkas (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2021)
The digital native generation is now exist in higher education as university students with their own identity or self-concept that has been formed with technology exposure since they born to the world. Undoubtedly, This condition present a gap between educators and students where each identity is formed according to their respective times. The purpose of this study is to understand the identity of the digital native generation as a basis for communicating with this group in the context of educational communication. It was conducted with library and Journals research approach related to Digital Native since the beginning of the term is used until its development to seek track record from the term of digital native utilization, critic and how they exist in higher education based on identity theory. Identity theory is used in this research by consideration that identity as communication product. The results show that the self-concept of the digital native generation is different from the previous generation, but this needs to be adjusted to the conditions of geographic or regional backgrounds which in fact have different technological exposure. The need for teachers' awareness that there is a new identity that is now present in the world of higher education with its identity. Knowing the digital native generation will help find strategies in appropriate learning communication in the delivery of teaching materials.